2005
DOI: 10.1002/bem.20149
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system tumours in children: Epidemiology and risk factors

Abstract: In children, a variety of distinct tumour types arise in the central nervous system (CNS) but they are frequently considered by epidemiologists as a single entity. CNS tumours are the second most common childhood malignancy and occur more frequently in developed countries than developing nations. Approximately 50% of paediatric CNS tumours are gliomas, with astrocytomas of the piloctyic type predominating. Distributions of subtypes by age show that primitive neuroectodermal tumours (PNET) and ependymomas mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 46 publications
1
40
0
3
Order By: Relevance
“…Conversely PNETs form a major group in children, but are rare in adults [39]. It is therefore likely that specific childhood and adult tumors have different aetiologies [40].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely PNETs form a major group in children, but are rare in adults [39]. It is therefore likely that specific childhood and adult tumors have different aetiologies [40].…”
Section: Discussionmentioning
confidence: 99%
“…Current thinking suggests that brain tumors develop in children as a consequence of accumulated genetic alterations that permit cells to evade normal regulatory mechanisms and destruction by the immune system. These alterations in the germ line may be inherited, but neurocarcinogens, agents of a chemical, biological, or physical nature, that damage DNA can lead to somatic mutations [2]. The causes of CNS cancers are largely unknown, but causes are likely to be both genetic and environmental.…”
Section: Introductionmentioning
confidence: 99%
“…In this age group, astrocytoma accounts for the 40% of tumors, followed by primitive neuroectodermal tumors (PNET) (22%), other gliomas (12%), other specified intracranial neoplasms (12%), and ependymoma (10%) [1]. Risk factors for CNS studied in adults may be different in children [2]. Current thinking suggests that brain tumors develop in children as a consequence of accumulated genetic alterations that permit cells to evade normal regulatory mechanisms and destruction by the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Although the increased risk of cancer or pregnancy outcome has not been conWrmed in epidemiological studies (Kheifets and Shimkhada 2005;McKinney 2005;Lagorio and Salvan 2001), recently the experimental and cellular studies have demonstrated that ELF-MF exposure can lead to chromosomal damage and gene destruction resulting in induction or promotion of cancer (Di Carlo et al 2002;Winker et al 2005;Scassellati et al 2004;Ivancsits et al 2002;Chen et al 2000). Some investigators suggest that DNA damage mechanism is an oxidative stress induced by ELF-MF (Strasak et al 2002, Yokus et al 2005Wolf et al 2005).…”
Section: Introductionmentioning
confidence: 93%